Implementasi Kegiatan Ekstrakurikuler Pramuka dalam Meningkatkan Karakter Nasionalisme Siswa Kelas IV SD Negeri 105345 Sidodadi Ramunia Kecamatan Beringin - Qoiria, Jihan; Ramadhan, Nuri; Ramadhani, Mastari (Medan Resource Center, 2024)
This study aims to examine: 1) the Indonesian language learning outcomes of students using the conventional teaching model at UPT SPF SD NEGERI 106800; 2) the learning outcomes of students using the CIRC (Cooperative Integrated Reading and Composition) learning model at the same school; and 3) the effect of the CIRC learning model on Indonesian language learning outcomes in class IV. The research employed a quantitative experimental approach with a quasi-experimental design (non-equivalent control group design) using pretest and posttest methods. Two classes were involved: an experimental class (class IV-A) with 15 students and a control class (class IV-B) with 15 students. The findings reveal a significant impact of the CIRC learning model on student learning outcomes. The average score of students in the experimental class using the CIRC model was 83.33, compared to 76.33 in the control class using conventional methods. The t-test results showed a significant difference with Sig. (2-tailed) < 0.05 (0.00 < 0.05), indicating the positive influence of the CIRC model on learning outcomes.